An Application to Wireless Standards for Remote Monitoring For Electric Drive Systems Using Zigbee Standards (International Journal of Scientific Research and Management (IJSRM), 2013)
This paper discusses an implementation of wireless standards for remote monitoring of electric drives. An appropriate wireless system has been developed and described. It uses ZigBee standard for remote data transmission combined with Internet connectivity for assessment of the Global network-collected information. The designed measuring devices and the respective sensors are also presented. Algorithms have been developed allowing evaluation of additional parameters using data from the measurements held. Detailed experimental studies confirm the good performance of this monitoring system. The research carried out as well as the results obtained can be used in design and set up of such types of wireless monitoring systems. Keywords––Intelligent sensors, End-device, Coordinator device, ZigBee network, Measurement system, Remote monitoring